The last driver's license holder has already been born : how rapid advances in automotive technology will disrupt life as we know it and why this is a good thing - Herger, Mario (McGraw-Hill, 2019)
"How the radical disruption of the auto industry affects you-and how you can prepare for the soon-to-be "new normal" The combined effect of autonomous driving, electric vehicles, and the sharing economy is on the verge of changing the auto industry-all within the next decade. And this tech/economics revolution will touch virtually every industry. What exactly will change? Jobs: Demand for commercial vehicle drivers, car dealers, mechanics, doctors, and many other professions will shrink Laws: Manually driving cars will be forbidden-and car ownership will be almost nonexistent Housing: Prices will drop and cities and towns will be planned differently Healthcare: Infrastructure will shrink as traffic accidents dramatically decline Global trade: China will become the world's biggest automotive exporter The Last Driver License Holder Has Already Been Born provides the information and insight you need to position your company for these groundbreaking changes. It reveals the disruptive technologies now taking shape and provides a timeline of when they will take hold. It examines the impact on the industry itself, as well as adjacent sectors, including jobs and professions, city and street design, hospitals, insurances, politics, security, hospitality industry, the oil industry, real estate, and society at large. And it provides the knowledge and insight you need to keep yourself and your organization ahead of the curve-and in front of the competition"--